Draft Seventh Five Year Plan Andhra Pradesh 1985-90 Volume II Section II Agriculture and Allied Services - Planning Commission (Planning Commission, 1985)
Andhra Pradesh continues to be a predominantly Agricultural State. About 80% of the population is dependent, on Agriculture for their livelihood. Forty seven percent of State’s income is generated from Agriculture sector. Thus Agriculture has become the main stay of State's economy. For improving the standard of living of such Vast percentage of people, Agricultural Development deserves high priority. Programmes designed to increase Agricultural production will not only help raise the income levels of rural population, but also generate considerable employment potential for the rural masses.
Finance and Planning (PLG. Wing) Department, Government of Andhra Pradesh
Finance and Planning (PLG. Wing) Department, Government of Andhra Pradesh